Group of Koli members standing for a group photo near the idol - Mumbai Archive Project Team (Jio Institute, 2024)
Koli boys gather for a group photo with the idol of the Goddess before it is taken for visarjan (immersion). The festival not only brings people together in a spirit of unity and joy but also serves as a reminder of the importance of preserving cultural heritage amidst the changing urban landscape of Mumbai.